Pengaruh Celebrity Endorsement, Brand Image Terhadap Purchase Intention pada Tiktok Shop - Rilasanti, Estu Aulia; Safuan (Economic Reviews Journal, 2025)
This study aims to analyze the effect of celebrity endorsement on consumer purchase intention in the TikTok Shop platform, with brand image as a mediating variable. The background of this research is driven by the growing popularity of social commerce, which encourages businesses to utilize digital marketing strategies through celebrity endorsements to build consumer trust and strengthen brand perception. The research employed a quantitative approach using an online survey of 120 active TikTok Shop users who had purchased skincare products. The instrument measured three main variables, namely celebrity endorsement, brand image, and purchase intention, using a Likert scale. Data analysis was conducted with Partial Least Squares Structural Equation Modeling (PLS-SEM) to test validity, reliability, and the relationships among variables. The results indicate that celebrity endorsement has a positive and significant effect on both brand image and purchase intention. Furthermore, brand image positively influences purchase intention and mediates the relationship between celebrity endorsement and purchase intention. These findings highlight the importance of selecting credible and relevant endorsers and maintaining a strong brand image so that digital marketing strategies on TikTok Shop can be more effective in enhancing consumer purchase intention.